Gut microbiota does not play a mediating role in the causal association between inflammatory bowel disease and several its associated extraintestinal manifestations: a Mendelian randomization study - Lu, Weipeng; Cen, Jiepeng; Dai, Qijie; Tao, Heqing; Peng, Liang (Frontiers in Immunology, 2024)
Background and Objectives: Observational study finds inflammatory bowel disease associated with multiple extraintestinal manifestations. To this end, we characterized the causal association between inflammatory bowel disease and extraintestinal manifestations through a Mendelian randomization study and further explore the role of intestinal flora between inflammatory bowel disease and the extraintestinal manifestations associated with it. Materials and Methods: We genetically predicted the causal relationship between inflammatory bowel disease and twenty IBD-related extraintestinal manifestations (Sarcoidosis, Iridocyclitis, Interstitial lung disease, Atopic dermatitis, Ankylosing spondylitis, Psoriatic arthropathies, Primary sclerosing cholangitis, Primary biliary cholangitis). We used a full GWAS summary statistics on gut microbiota in 18340 participants from 24 cohorts to explore its role in the casual relationships between IBD and IBD-related extraintestinal manifestations. Inverse variance weighted (IVW) are used as the main analytical method to assess the causal associations. We performed Cochran's Q test to examine the heterogeneity. To assess the robustness of the IVW results, we further performed sensitivity analyses including weighted median method, MR-Egger regression, Mendelian Randomization Pleiotropy RESidual Sum and Outlier (MR-PRESSO) test. The leave-one-out sensitivity analysis is further performed to monitor if significant associations were dominated by a single SNP. Result: A total of eight extraintestinal manifestations were found to be at elevated risk of developing due to inflammatory bowel diseases. A total of 11 causal relationships were found between IBD and gut microbiota, four of which were stable. Between gut microbiota and these 8 extraintestinal manifestations, a total of 67 nominal causal associations were identified, of which 13 associations were stable, and notably 4 associations were strongly correlated.Through the two-sample MR analysis, we identified extraintestinal manifestations that were causally associated with inflammatory bowel disease and obtained multiple associations from inflammatory bowel disease and gut microbiota, and gut microbiota and extraintestinal manifestations in further analyses. These associations may provide useful biomarkers and potential targets for the pathogenesis and treatment.